Impact of Writing Learning Model Flipped Classroom Based on Video on the Writing Ability and Quality of Procedural Text Components - Habiburrohman Haidar; Gunawan Suryoputro; Imam Safi’i (Jurnal Pendidikan Indonesia, 2026)
This study was motivated by the majority of junior high school students who were still having difficulty writing procedure text. The purpose of this study is to test the impact of video -based class learning models on the ability to write and the quality of procedure text components. The method used is quasi-experimental involving 250 junior high school students with each group of 125 students. Data collection methods using the writing assessment rubric instrument include content, organization, vocabulary, language, and sentence use. Data analysis using nonparametric tests, namely Mann-Whitney and Wilcoxon Signed Rank Tests. Research findings show video -based class -based class models combined with online classes have a more significant impact on the quality of student writing components and writing skills compared to conventional learning. The component that shows the most significant increase is the organizational component, followed by language and vocabulary components. Components that have increased at least are sentence mechanics. This finding shows that intervention can improve student quality and writing skills. The implication of this study is the integration of feedback with the media is able to create an innovative and effective learning process in improving writing skills.